Aspekty cywilnoprawne procesu planowania przestrzennego - Pilarz, Karina (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
Administrative law permeates with other areas of law, including civil law. We can also observe these relationships in the field of spatial planning. An example of these relations are civil law agreements concluded by planning authorities, protection of property rights and civil law claims in connection with the adoption or amendment of a local plan.
Keywords: civil claims; spatial planning; property rights; civil contract